A Comparative Study Of The Direct Appointment Process For Construction Service Providers Under Presidential Decree No. 16 Of 2018 And Presidential Decree No. 12 Of 2021 (Case Study: Gunung Rajak Village Library Construction Project) - Ilham Yakup; Hafiz Hamdani; Adiman Fariyadin (International Journal of Science and Environment (IJSE), 2025)
Construction work is an important part of economic growth. Procurement of construction goods and services is one of the factors for successful development. One method used in procurement of construction services is direct appointment. Based on this, the government issued Presidential Regulation No. 16 of 2021 and Presidential Regulation No. 12 of 2021 concerning procurement of construction goods and services. The purpose of this study is to determine the stages of the direct appointment process and to determine the impact of changes in presidential regulations on the process of direct appointment of construction service providers. Thus, it is hoped that it can provide policy recommendations that can increase the effectiveness of construction service procurement. The research method uses quantitative descriptive research. The sampling technique uses purposive sampling, with data taken from the Gunung Rajak Village Library Building Construction project and questionnaires distributed to service providers, service providers, and the Gung Rajak village community who understand service procurement. The data processing is descriptive and the questionnaire data processing uses a Likert Scale. The results of this study are that the process of direct appointment activities in the Gunung Rajak village library building construction project was carried out well and structured. Then the results of the questionnaire analysis with a Likert Scale showed the percentage value of the respondents' attitudes above 80%, with a small standard deviation value, namely (between 0.626 - 0.484), and an average Likert scale value of 4. These results indicate that Presidential Regulation No. 12 of 2021 is considered better in the process of direct appointment of construction service providers compared to Presidential Regulation No. 16 of 2018.